The n-dig-Cyclization (n = 5, 6) of Alkynes Involving Fixation of CO2 - Wang, Bingbing; Sun, Song; Cheng, Jiang (Synlett, 2018)
Being an abundant, easily available, and renewable one-carbon source, carbon dioxide has received much attention in organic synthesis. However, carbon dioxide is a thermodynamically inert molecule that is hard to incorporate into useful chemicals. Nevertheless, various elegant methods have been developed for the incorporation of carbon dioxide in a number of heterocycles. In this review, we summarize and update the recent advances in n-dig-cyclization of alkynes involving the fixation of CO2, including the 5-dig- and 6-dig-cyclization of alkynes.1 Introduction2 The 5-dig-Cyclization of Alkynes3 The 6-dig-Cyclization of Alkynes4 Conclusion
Keywords: alkynes; CO2 fixation; cyclization; rearrangement; multicomponent reaction